Process of Renewal in a Company in Crisis : a Case Study - Szpikowski,Tomasz (Proces odnowy w przedsiębiorstwie przechodzącym kryzys : studium przypadku, 2010)
The article describes the crisis that occurred in a specific organization which operates in Central Europe and employs several thousands of people there. As a consequence of the difficult economic situation, the process of Renewal had to be applied to change the operating strategy of the company and refresh the processes that directly influence its financial stance. Specific activities related to the acquisition strategy, the implementation of new business lines and building strong leadership for the company as well as ensuring financial stability after the crisis are depicted in this article. Eventually, the implementation of the described actions led to strengthening of the company's leading position in Poland and abroad.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 144-152
Keywords: corporate renewal; case study; crisis